REMOTE, SMARTPHONE APP-BASED ASSESSMENT OF NORMAL AND DUAL TASK WALKING IN HEALTHY YOUNGER AND OLDER ADULTS. (11th November 2018) - Yu, W; Zhu, H; Lo, O; Zhou, J; Harrison, R; Lipsitz, L; Pascual-Leone, A; Manor, B
Abstract: The ability to walk under normal and cognitive dual task conditions is essential for safe mobility in older adults. However, while assessments of gait provide important health information, they have been limited to laboratory settings. We aimed to create an easy-to-use smartphone App enabling remote dual task walking assessments, and to demonstrate its reliability and validity in relatively healthy younger and older adults. The iPhone-based App utilized multi-media instructions and the phone's internal motion sensors to record movements during normal walking and walking with simultaneous serial-subtractions, with the phone placed in the user's pants pocket. Fourteen younger and 12 older adults completed two lab visits, during which data were acquired by the App and GAITRite mat over multiple normal and dual task walking trials. Participants also used the App to complete assessments in their homes on three separate days. Outcomes included average stride time and the dual-task cost to stride time. Across all detected strides in laboratory trials, derived outcome measures from the App were highly correlated with those derived from the GAITRite mat (Stride Time: p<0.001, r2 =0.99. Dual-task cost: p<0.001, r2 =0.98). These correlations were unaffected by age group, walking condition, and pocket tightness. Moreover, across trials, gait metrics demonstrated excellent test-retest reliability, both within and between laboratory visits and home-based assessments (ICC: 0.79–0.90). These results suggest that dual task walking assessments are valid and can be reliably administered in remote settings in relatively healthy younger and older adults.